Analysis of the labor consumption and duration of the assembly processes of structural coating plates blocks using the crane method - Sobko, Y.T.; Novak, Y.V. (Ways to Improve Construction Efficiency, 2022)
The labor intensity of the construction process is determined by the methods of technical standardization of processes by the methods of time tracking. On the basis of these observations, regulations are developed in the form of GN or other collections of norms of labor costs. Labor intensity is measured in person–hours, and the rate of labor costs is derived from the rate of time, taking into account the number of performers. Variants of consolidation and installation of structural plates of the covering are not typical. The main processes necessary for the duration and labor–intensiveness of the structural slabs of the coating by the free method have been analyzed. A potential development has been identified that will ensure a reduction in the labor–intensiveness of the assembly process and provide cyclical assembly work. The consolidation process is optionally performed on the assembly stand, which belongs to the assembly equipment equipment. To install the stand, a site is specially prepared in the form of a horizontally planned surface of the earth with a layer of compacted crushed stone. Cells made of wooden sleepers are placed on the crushed stone, which are set according to vertical planning marks with the help of geodetic devices. Then a collection stand is installed on the sleeping cells. Structurally, the stand consists of several parts. That is why the manufacturability of the installation of the structural plates of the covering was improved by means of constructive and technological solutions. First, the columns are mounted (columns with a height of 12 m were used for the analysis), so it is not possible to carry out consolidation in the area of the columns. The stands are placed next to each other in the working area of the crane. All calculations were performed in tabular form according to the formula. The installation process of 12 m high columns includes the sub–processes of unloading and disassembly, installation and fastening. The components of these processes are actions (operations). According to the methodology, a schedule of the processes of consolidation and installation of blocks of structural slabs with preliminary installation of columns according to the corresponding calculations was built.